IMPLEMENTASI DATA MINING DALAM PREDIKSI KINERJA KEUANGAN DAN OPERASIONAL PADA PERUSAHAAN AVIASI MENGGUNAKAN LINEAR REGRESSION - Andika Juwita Nugroho; Entis Sutrisna (CV. Multi Kreasi Media, 2023)
PT. Angkasa Pura I is a subsidiary of Aviation Tourism Indonesia which is one of the Aviation companies engaged in the design, development, and manufacturing of aircraft in Indonesia in the batam island, central and eastern Java and Bali, Lombok Island, West Timor, Southern and Eastern Kalimantan, Northern and Southern Sulawesi, Ambon Island and Papua. In its management, this company has financial and operational performance to predict financial and operational performance in the future, making it easier for companies to assess financial and operational performance to remain stable. This is useful for minimizing losses. In fact, there are many prediction errors in a manual way influenced, one of which is by human miscalculations. This will of course be fatal to the company. In addition, manual predictions will certainly drain time, mind, and energy resources when the calculated data is large in number. Therefore, based on the problems that occur, researchers will implement data mining to predict financial and operational performance in aviation companies using Simple Linear Regression. The result of this study is a system that can predict financial and operational information as a source to support strengthening in decision making, especially from the company's financial side.